Black Phosphorus Nanosheets for Killing Bacteria through Nanoknife Effect. (14th July 2020) - Guo, Tao; Zhuang, Shihao; Qiu, Honglong; Guo, Yating; Wang, Lili; Jin, Guixiao; Lin, Weiwen; Huang, Guoming; Yang, Huanghao
Abstract: Black phosphorus (BP) has emerged as a rapidly rising star in the field of biomedical science. In this work, BP nanosheets (BPNSs) are synthesized and their potential as a nano‐antibacterial agent is investigated. The concentration and time‐dependent antibacterial activities are evaluated by cell viability assays together with scanning electron microscopy, confocal laser scanning microscope, and the measurement of efflux of RNA release assay. The experimental results show that BPNSs have a strong killing effect on both representatives of gram‐negative bacteria ( Escherichia coli ) and gram‐positive bacteria ( Staphylococcus aureus ), and exhibit concentration and time‐dependent antibacterial activity. The sharp edges of BPNSs in the interaction with bacteria can cause physical damage to the bacterial membrane and RNA leakage, resulting in bacterial death. The results demonstrate that the BPNSs show great promise as new nano‐antibacterial materials. Abstract : The potential of black phosphorus nanosheets (BPNSs) as an antibacterial agent is investigated. BPNSs can efficiently kill both gram‐positive and gram‐negative bacteria through nanoknife effect. The direct insertion of BPNSs into bacteria causes the physical damage of the bacterial membrane and the subsequent release of intracellular contents, leading to the eventual death of bacteria.